Memahami Persepsi Brand Equity Dari Sisi Commited Customer Serta Perjalanan Keputusan Memilih Aplikasi Traveloka (Studi Deskriptif Kualitatif Berdasar Customer Based Brand Equity Pada Aplikasi Traveloka) - Fafan Suryo Nugroho; Hedi Pudjo Santosa (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
This research aims to understand Brand Equity Perception From Commited Customer Perspective and Decision Journey Choosing Traveloka Application. This research is conducted following the presence of many critical reviews on Traveloka application in Google Play Store. This study is completed using descriptive qualitative method. The main theory of this study is Process Response Theory along with consumer decision journey framework in particular. The data collection method is conducted through in-depth interview of 6 informants. From the observation, it was found that committed customers assess four points based on customer based brand equity. The evaluation of committed customers reveals that the quality Traveloka delivers is excellent. They can also identify it further by mentioning that Traveloka application offers different kinds of travel necessity, like Fix Price or Traveloka Points. Lastly, they fall into the commited customers category, which means they are very loyal to Traveloka application and never tried any of its competitors. In their respective Traveloka application usage some of these commited customers undergo completely the six points decision journey but there are some of them who also goes through several steps that they should have completed before deciding to use the product, which is Traveloka application.